Factores de riesgo de mal desenlace funcional en pacientes hospitalizados por hemorragia intracerebral espontanea en un Hospital de referencia de Piura - Terrones-Calle , Nathaly M. (2025)
Aim: To evaluate the risk factors for poor functional prognosis in patients hospitalized for spontaneous intracerebral hemorrhage. Methods: A retrospective cohort study was carried out where 73 patients with a diagnosis of intracerebral hemorrhage were included in a reference hospital in Peru from 2020 to 2022. The clinical history was used, which included demographic, clinical, laboratory and imaging data. Associations between qualitative variables and the incidence of poor functional outcome and mortality were established using Pearson's chi-square test, crude relative risks (RRc) with 95% confidence intervals were used, and a Poisson linear model with a function was applied. log link and robust variances. Results: 66.7% experienced poor functional outcome, the associated factors were: previous cerebrovascular disease, Glasgow Coma Scale on admission from 3 to 8, leukocyte level, early neurological deterioration, and in-hospital complications. 36.1% of patients died where it was associated with: Glasgow Coma Scale on admission from 3 to 8, early and late neurological deterioration, elevated levels of leukocytes, glucose and in-hospital complications. Conclusion: In patients with intracerebral hemorrhage, it is associated with a high rate of poor functional outcome and mortality.